Investigation of the Suitability of Karadere River (Araklı-Trabzon) for Drinking and Irrigation Purposes - Arzu Fırat Ersoy; Esra Hatipoğlu Temizel (Doğal Afetler ve Çevre Dergisi)
In this study, it was aimed to determine the water quality characteristics of Karadere River. For this purpose, physical parameters, major anion-cation and trace element analyzes were carried out by performing surface water sampling in Karadere River. In order to determine the hydrochemical properties, two periods of surface water sampling were carried out in October-2020 and April-2021. The physical properties, major anion and cation analysis results of the water samples were evaluated according to the World Health Organization WHO, TS266 (Regulation on Water Intended for Human Consumption) and Water Pollution Control Regulation. Water types in Karadere surface water were determined as Ca-HCO3 and Ca-Na-HCO3. It has been determined that Karadere surface water is suitable for drinking water in terms of this physical parameters and major anions-cations according to WHO and TS266 Regulation on Water Intended for Human Consumption. According to the Water Pollution Control Regulation, all parameters were determined to be in I and II water class. When examined in terms of pollution, it is seen that Karadere surface water is in IV class water class according to NO2 content. It has been determined that the Al and Fe values of the rainy period in terms of trace element contents are above the limit values defined in the TS266 Regulation on Water Intended for Human Consumption. It has been determined that Karadere surface water can be used in agricultural activities in all plants except for plants that are sensitive to sodium and in plants that need moderate salt.